The Molecular Diversity-based ISSR of Durio tanjungpurensis Originating from West Kalimantan, Indonesia - Riupassa, Pieter Agusthinus; Chikmawati, Tatik; Miftahudin,; Suharsono, (UI Scholars Hub, 2015)
The Durian Tengkurak (Durio tanjungpurensis Navia) is one of the endangered exotic species in the Malvaceae family. The species is important for conservation of the germplasm and is considered a potential genetic resource for the development of durian in the future. The objective of this research project was to assess the molecular diversity of D. tanjungpurensis in West Kalimantan, based on Inter Simple Sequence Repeat (ISSR) markers. We applied ten ISSR primers to reveal the genetic diversity of 60 individuals from six natural endemic D. tanjungpurensis populations. The genetic diversity parameters were estimated based on binary data about PCR products (present or absent bands). The results showed that the mean number of observed alleles, the mean number of effective alleles, the genetic diversity, the Shannon’s Information Index score, the number of polymorphic loci, and the percentage of polymorphic loci were 1.53, 1.29, 0.17, 0.26, 77.83, and 52.59, respectively. An analysis of molecular variance (AMOVA) showed that the genetic diversity within a population (65%) was higher than that found between the populations (35%). UPGMA clustering and principal coordinate analysis, based on the DICE similarity matrix, were used to classify the populations into three groups: 1) Hutan Rejunak and Tembaga, 2) Bukit Merindang, and 3) Hutan Rawak, Bukit Sagu 1, and Bukit Sagu 2. Further analysis of the population structure using STRUCTURE software was used to classify all the individuals into two major categories, thus uniting Groups 2 and 3 as one major category. In conclusion, a high level of genetic diversity in the Durian Tengkurak was revealed utilizing the ISSR markers employed in the study.